Transboundary Trajectory Patterns of PM2.5 in The Lower Troposphere of Jakarta Region - Istiqomah, Sifa; Santikayasa, I Putu; Turyanti, Ana (Agromet, 2025)
PM2.5 is a key indicator of air quality and poses serious environmental and health concern, especially in Jakarta where air quality frequently exceeds recommended standards. But researches mainly focus on surface-level pollutant, underscoring transboundary emission. This study aims to analyze the transboundary trajectory patterns of PM2.5 pollutants, and to estimate the contribution of emissions to air quality in the Jakarta for 2024. Meteorological data and PM2.5 concentrations from five air quality monitoring stations were analyzed during non-rainfall periods. Potential emission sources analysis was simulated using HYSPLIT Concentration Weighted Trajectory (CWT). Our results show PM2.5 concentrations during the wet season were ~40% lower than dry season, with an average concentration of 27.11 μg/m3 and were strongly influenced by monsoonal wind patterns in both seasons. During the west monsoon, pollutant transport was predominantly from the southwest to northeast, whereas during the east monsoon it shifted from the northwest to northeast. The trajectory patterns exhibited no substantial differences across all layers (15, 50, 100, and 200 m), although seasonal atmospheric stability influenced pollutant dispersion. In the wet season, PM2.5 primarily originated from western regions of Jakarta, while in the dry season sources were predominantly from the east, which is consistent with prevailing monsoonal winds. Several monitoring stations also indicated potential contributions from North Jakarta due to curved airflow patterns. These findings highlight the dominant role of monsoonal wind in controlling PM2.5 concentrations and transboundary transport in Jakarta within the lower troposphere.